Spectral Fidelity of Earth's Terrestrial and Aquatic Ecosystems. Issue 8 (9th August 2021) - Thompson, David R.; Brodrick, Philip G.; Cawse‐Nicholson, Kerry; Dana Chadwick, K.; Green, Robert O.; Poulter, Benjamin; Serbin, Shawn; Shiklomanov, Alexey N.; Townsend, Philip A.; Turpie, Kevin R.
Abstract: The Surface Biology and Geology (SBG) investigation will create global maps of spectral surface reflectance and emissivity at a cadence of 16 days or better, with coverage to address global questions about Earth's geology, cryosphere and ecosystems. The revolutionary potential poses a commensurate challenge: creating contiguous maps free from regional biases induced by atmosphere, observation geometry, or inversion error. This will require an accurate calibration with precise knowledge of each channel's spectral response. Here, we quantify the impact of spectral calibration on SBG's aquatic and terrestrial ecosystem objectives. We find that contemporary algorithms for ecosystem trait retrieval demand more accurate spectral calibration than historical missions. Errors due to drift or spatial nonuniformity in the wavelength calibration that have previously been considered acceptable can cause systematic errors larger than the instrument noise and of the same order as the variability SBG aims to measure. Moreover, their impact on atmospheric correction can induce climate‐dependent systematic errors that thwart comparisons between ecosystems. These results underscore the importance of spectral response accuracy in SBG mission design. Plain Language Summary: Remote imaging spectrometers operating in visible to shortwave infrared wavelengths of the electromagnetic spectrum measure the intensity of solar‐reflected light as hundreds of distinct channels. This requires knowing the precise spectral range to which each channel is sensitive. The accurate association of wavelengths to instrument channels is known as the spectral calibration of the instrument, or simply spectral fidelity . Small errors in this calibration can have a significant impact on measurement accuracy. This study evaluates the sensitivity of a future global investigation of Earth's ecosystems to such errors. We find that small errors in spectral calibration can cause large inaccuracies in maps of ecosystem properties. This means that accurate spectral calibration will be critical for the success of these future investigations. Key Points: The spectrometer of NASA's Surface Biology and Geology investigation will need precise spectral calibration Wavelength calibration errors previously considered acceptable could result in measurement distortions far greater than the instrument noise Wavelength calibration inaccuracy can induce humidity‐dependent biases, thwarting efforts to compare ecosystem traits across regions